PENGARUH FAKTOR FUNDAMENTAL, RISIKO SISTEMATIS DAN EKONOMI MAKRO TERHADAP RETURN SAHAM SYARIAH YANG TERGABUNG DI JAKARTA ISLAMIC INDEX (JII) PADA PERIODE 2010 – 2014 - Hasanah Setyowati; Riyanti Ningsih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This study aimed to obtain empirical evidence on the influence of fundamental factors, systematic risk and macroeconomics on the returns Islamic stock of companies incorporated in the Jakarta Islamic Index in 2010-2014. The variables used were the fundamental factors that are proxied by Earning Per Share (EPS), Return on Equity (ROE), Debt to Equity Ratio (DER); Systematic risk is proxied by Beta Shares; macroeconomic factors is proxied by the inflation rate and the exchange rate. The samples of this study are the enterprises incorporated in Jakarta Islamic Index (JII) at the Indonesian Stock Exchange. The sampling method was using purposive sampling. There were 12 samples of Islamic stocks that meet the criteria to be used as samples. The analysis model used is multiple linear regression techniques and the type of data used is secondary data. The study found that all variables, which are Earning Per Share (EPS), Return on Equity (ROE), Debt to Equity Ratio (DER), Beta stock, inflation and the exchange rate do not significantly affect the return of sharia stock either simultaneously or partially.